ECONOMIC GROWTH AND EMPLOYMENT IN AGRICULTURAL SECTOR ON POVERTY IN ACEH PROVINCE - Reovasimulo Anakusara; Abd Jamal; Chenny Seftarita; Indra Maipita (TRIKONOMIKA, 2019)
This empirical study aims to analyze the impact of economic growth and employment in the agricultural sector on poverty in Aceh Province. The study is conducted on annual time series data for the period of 1995-2017 while to explain the research objectives used Autoregressive Distributed Lag (ARDL) model and Granger Causality. The results found, in the short term, only employment in the agricultural sector has a significant effect on poverty. Meanwhile, in the long term, economic growth has a profound and negative impact on poverty. On the contrary, the absorption of labor in the agricultural sector tends to increase poverty. In addition, the results obtained that economic growth has a unidirectional relationship with employment in the agricultural sector. It was, therefore, suggested that the government should prioritize economic development in regions that have relatively high poverty rate and build an agro-industry in Aceh to increase agricultural value added and also absorb more labor so it can enable to reduce the poverty rate.